PENGARUH PROMOSI ONLINE DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA URBAN KAKTUS DAN SEKULEN DI JAKARTA TIMUR - Halimah Athiyyah Arbah; Syahrul Reza (JAMBIS : Jurnal Administrasi Bisnis, 2022)
This study aims to determine online promotions and prices effects on purchasing decisions on Urban Cactus and Succulent in East Jakarta. The population used in this study is infinite, namely all consumers of urban cactus and succulent products in East Jakarta. The sampling technique used is nonprobability with a sample of 185 samples. Analysis of the data used is a multiple linear regression analysis using IBM Statistics software version 25. Through quantitative research methods, data collection techniques in questionnaires form, and literature review, this study shows that online promotions influence purchasing decisions by 66.0%. Price also influences purchasing decisions by 68.7%. Thus, online promotions and price affect purchasing decisions at Urban Cactus and Succulent in East Jakarta significantly. They affect the purchasing decision variables simultaneously with a value of 0.747 or 74.7% of which 25.3% is influenced by other factors not examined inthis study.